HERMENEUTICS OF THE QUR'AN IN DIGITAL SPACE: DISCOURSE ANALYSIS OF INTERPRETATION AND RELIGIOUS AUTHORITY - Ishak Hariyanto; Apipuddin (Tahiro : Journal of Peace and Religious Mederation, 2025)
Digital transformation has reshaped how Muslims access, interpret, and share the Qur'an. If previously interpretation was dominated by scholars through classical texts and formal forums, today the digital sphere enables the rise of new authorities fluid, populist, and often detached from traditional scholarship.This paper explores Qur'anic hermeneutics in digital spaces by examining interpretive discourses and the construction, negotiation, and contestation of religious authority. Using critical discourse analysis, the study investigates practices on social media, YouTube, and digital da'wah platforms to uncover underlying power relations, ideological currents, and strategies of legitimacy. Findings reveal that the digital realm is not merely a medium of dissemination, but a contested arena where classical traditions, puritan currents, progressive interpretations, and lay voices intersect. This dynamic simultaneously fosters democratization of interpretation while risking fragmentation of authority and trivialization of meaning. Hence, Qur'anic hermeneutics in the digital age requires a critical framework attentive to textual, socio-political, and technological dimensions.